2017
DOI: 10.1016/j.omtm.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

A New Broad Range Plasmid for DNA Delivery in Eukaryotic Cells Using Lactic Acid Bacteria: In Vitro and In Vivo Assays

Abstract: Lactococcus lactis is well documented as a promising candidate for development of novel oral live vaccines. It has been broadly engineered for heterologous expression, as well as for plasmid expression vector delivery, directly inside eukaryotic cells, for DNA vaccine, or as therapeutic vehicle. This work describes the characteristics of a new plasmid, pExu (extra chromosomal unit), for DNA delivery using L. lactis and evaluates its functionality both by in vitro and in vivo assays. This plasmid exhibits the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 45 publications
2
37
0
Order By: Relevance
“…For this last application it was shown that both, native and invasive L. la ctis, can be used as in vitro and in vivo DNA delivery vehicles for plasmid transfer into mammalians cells (Guimaraes et al, 2006; Chatel et al, 2008; Innocentin et al, 2009; Almeida et al, 2014; Mancha-Agresti et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…For this last application it was shown that both, native and invasive L. la ctis, can be used as in vitro and in vivo DNA delivery vehicles for plasmid transfer into mammalians cells (Guimaraes et al, 2006; Chatel et al, 2008; Innocentin et al, 2009; Almeida et al, 2014; Mancha-Agresti et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…The B. subtilis bactofection mechanism in shrimp could be similar to the Lactococcus lactis, a gram-positive lactic acid bacterium, bactofection mechanism in mice [38]. B. subtilis probably adheres to epithelial cells and enters the cell by internalization of a vacuole/phagosome.…”
Section: Discussionmentioning
confidence: 99%
“…New vectors had been developed to approach the DNA vaccine using LAB as live delivery vehicles [146,147,[148][149][150]. These vectors present a series of common characteristics such as the presence of a eukaryotic promoter, which allows protein expression by eukaryotic cells; a prokaryotic region, which has a selection marker (usually antibiotic resistance); a multiple cloning site, where the open reading frame (ORF) of interest will be inserted; and a prokaryotic origin of replication, which ensures that the plasmid replicates only in prokaryotic cells [151].…”
Section: Lab As a Live Vehicle To Deliver Dna Vaccine Plasmids To Eukmentioning
confidence: 99%
“…These vectors present a series of common characteristics such as the presence of a eukaryotic promoter, which allows protein expression by eukaryotic cells; a prokaryotic region, which has a selection marker (usually antibiotic resistance); a multiple cloning site, where the open reading frame (ORF) of interest will be inserted; and a prokaryotic origin of replication, which ensures that the plasmid replicates only in prokaryotic cells [151]. Some molecules (IL-10, IL-4, and HSP65) have been cloned in these vectors to evaluate their effect, especially as a treatment approach in diseases related to the bowel [152,153], as well as reporters (GFP and Cherry) which allowed the understanding of this platform in the mammalian body [148,154]. Although further studies need to be conducted in order to elucidate whether the cloning of ORFs of interest in these vectors is really effective pointing to disease prevention and treatment, this approach is undoubtedly an important tool for the development of new techniques with potential in the medical clinic.…”
Section: Lab As a Live Vehicle To Deliver Dna Vaccine Plasmids To Eukmentioning
confidence: 99%